Milky Way mass with K giants and BHB stars using LAMOST, SDSS/SEGUE, and Gaia: 3D spherical Jeans equation and tracer mass estimator. Issue 1 (23rd July 2022) - Bird, Sarah A; Xue, Xiang-Xiang; Liu, Chao; Flynn, Chris; Shen, Juntai; Wang, Jie; Yang, Chengqun; Zhai, Meng; Zhu, Ling; Zhao, Gang; Tian, Hai-Jun
ABSTRACT: We measure the enclosed Milky Way mass profile to Galactocentric distances of ∼70 and ∼50 kpc using the smooth, diffuse stellar halo samples of Bird et al. The samples are Large Sky Area Multi-Object Fiber Spectroscopic Telescope (LAMOST) and Sloan Digital Sky Survey/Sloan Extension for Galactic Understanding and Exploration (SDSS/SEGUE) K giants (KG) and SDSS/SEGUE blue horizontal branch (BHB) stars with accurate metallicities. The 3D kinematics are available through LAMOST and SDSS/SEGUE distances and radial velocities and Gaia DR2 proper motions. Two methods are used to estimate the enclosed mass: 3D spherical Jeans equation and Evans et al. tracer mass estimator (TME). We remove substructure via the Xue et al. method based on integrals of motion. We evaluate the uncertainties on our estimates due to random sampling noise, systematic distance errors, the adopted density profile, and non-virialization and non-spherical effects of the halo. The tracer density profile remains a limiting systematic in our mass estimates, although within these limits we find reasonable agreement across the different samples and the methods applied. Out to ∼70 and ∼50 kpc, the Jeans method yields total enclosed masses of 4.3 ± 0.95 (random) ±0.6 (systematic) × 10 11 M⊙ and 4.1 ± 1.2 (random) ±0.6 (systematic) × 10 11 M⊙ for the KG and BHB stars, respectively. For the KG and BHB samples, we find a dark matter virial mass of M_200=0.55^+0.15_-0.11 (random) ±0.083 (systematic) × 10 12 M⊙ and M_200=1.00^+0.67_-0.33 (random) ±0.15 (systematic) × 10 12 M⊙, respectively.